Interactive effects of warming and microplastics on metabolism but not feeding rates of a key freshwater detritivore. (December 2019) - Kratina, Pavel; Watts, Tania J.; Green, Dannielle S.; Kordas, Rebecca L.; O'Gorman, Eoin J.
Abstract: Microplastics are an emerging pollutant of high concern, with their prevalence in the environment linked to adverse impacts on aquatic organisms. However, our knowledge of these impacts on freshwater species is rudimentary, and there is almost no research directly testing how these effects can change under ongoing and future climate warming. Given the potential for multiple stressors to interact in nature, research on the combined impacts of microplastics and environmental temperature requires urgent attention. Thus, we experimentally manipulated environmentally realistic concentrations of microplastics and temperature to partition their independent and combined impacts on metabolic and feeding rates of a model freshwater detritivore. There was a significant increase in metabolic and feeding rates with increasing body mass and temperature, in line with metabolic and foraging theory. Experimental warming altered the effect of microplastics on metabolic rate, which increased with microplastic concentration at the lowest temperature, but decreased at the higher temperatures. The microplastics had no effect on the amount of litter consumed by the detritivores, therefore, did not result in altered feeding rates. These results show that the metabolism of important freshwater detritivores could be altered by short-term exposure to microplastics, with greater inhibition of metabolic rates at higher temperatures. The consequences of these metabolic changes may take longer to manifest than the duration of our experiments, requiring further investigation. Our results suggest little short-term impact of microplastics on litter breakdown by gammarid amphipods and highlight the importance of environmental context for a better understanding of microplastic pollution in freshwater ecosystems. Graphical abstract: Image 1 Highlights: Metabolic and feeding rates of detritivores increase with body mass and temperature. Microplastics pollution reduces metabolic rates but not feeding rates. Experimental warming alters the effect of MPs on metabolic rates. Increased MP concentrations only inhibited metabolism at the highest temperatures. Effects of MPs on organismal physiology thus depend on environmental context. Abstract : Results summary: Warming alters the effect of microplastics on metabolic rates. Increased microplastic concentrations only inhibited metabolism at the highest temperatures.